Nitrogen Regulator GlnR Controls Redox Sensing and Lipids Anabolism by Directly Activating the whiB3 in Mycobacterium smegmatis - You, Di; Xu, Ying; Yin, Bin-Cheng; Ye, Bang-Ce (Frontiers in Microbiology, 2019)
WhiB3 is a conserved cytoplasmic redox sensor which is required in the infection and lipid anabolism of Mycobacterium tuberculosis. The response of WhiB3 to environmental nutrient and its regulatory cascades are crucial during the persistent infection, while little is known about the relationship between WhiB3 and emergence of nutrient stress in this process. Here, we found that nitrogen regulator GlnR directly interacted with the WhiB3 promoter region and activated its transcription in response to nitrogen availability. In whiB3 promoter region, the typical GlnR-box was also identified. Moreover, GlnR controlled cell resistance to redox stress and SL-1 lipid anabolism by directly activating whiB3 expression. These results demonstrated that GlnR regulated redox sensor WhiB3 at the transcriptional level and mediated the interplay among nitrogen metabolism, redox sensing, and lipid anabolism.